(untitled) (Marketing Journal, 2025)
This scientific article explores the theoretical and practical aspects of the use of transformation processes in the organization of tourism services, dynamic changes taking place in the tourism market, increased competition, widespread use of digital technologies and changes in tourist needs. Scientific and practical problems and solution proposals that serve to radically update the tourism sector and adapt to world № 10-SON OKTA BR, 2025 -YIL 632 standards have been considered in Uzbekistan. In the organization of tourism services, conclusions have been developed on the need to systematize transformation processes and the prospects for the development of tourism as a strategic area.